(untitled) (European Bison Conservation Newsletter, 2011)
This study was aimed at providing a description of the morphology and metric evaluation of reproductive organs of a female bison. Its additional objective was to track changes proceeding in the structure of these organs depending on age and sexual maturity of the animals. An attempt was also undertaken for a comparative analysis of those organs with these of domestic cattle. The experimental material were reproductive organs of 55 females of Lowland European bison inhabiting the Białowieża Forest. The animals were divided into two age classes, including females aged 2 months to 1.5 year (group I) and the sexually matured ones aged 2 to 20 years (group II). Observations were made and description was provided of the vagina, its vestibule and external reproductive organs. In order to analyze microscopic structures, samples of particular tissues were collected for histological examinations. The preparations were stained with a reference HE method. Results obtained were subjected to metric analysis and compared with respective values reported for domestic cattle. The structure of the reproductive organs of female bison is usually similar to that of domestic cattle, however their dimensions are smaller. The organs display structural characteristics that may be linked with specific seasonality of the reproductive cycle of the species.